Pengaruh dukungan manajerial puncak dan kepercayaan atas teknologi sistem informasi akuntansi terhadap kinerja individual dengan kemudahan penggunaan sebagai variabel moderasi - Solikhati Sobri (AKT 14 UMY 058, 2014)
This research is aimed to determine the effect of top management support and reliance in the accounting information system technology to individual performance and Ease of Use as a moderating variable. Sampling was purposive sampling method. Samples were obtained were 112 respondents part employee accounting or financial services company in the city of Yogyakarta and Sleman. Respondents were asked to complete a questionnaire that was given in the form of a questionnaire. The questionnaire was tested with reliability test and validity test. The next testing of classical assumptions covers multicollinearity test, the normality test and heteroscedasticity test. Test hypothesis in this research using a multiple linear regression test by using the Moderate Regression Analysis (MRA) or test the interaction with the program Statistical Package for Social Sciences (SPSS) version 15.0 for windows evaluation. The results showedthattop management supportdoes noteffect onindividual's performance. reliance in theaccounting informationsystemtechnologyaffectsindividual performance. Easeof usedoes notmoderate the relationshipof top managementsupportaboveaccounting informationsystemtechnologytoindividual performance. Easeof usemoderate the relationshipof trustover theaccounting informationsystemtechnologytoindividual performance. Keywords: top management support, trust, accounting information systems technology, individual performance and ease of use.